1994
DOI: 10.1007/bf00335179
|View full text |Cite
|
Sign up to set email alerts
|

Giant syringobulbia in childhood

Abstract: A case of giant syringobulbia with syringomyelia extending to the upper dorsal region is reported. The case occurred in a 3.5-year-old girl who presented with a history of frequent bouts of severe pain in the lower neck and the shoulder blades. Simple decompression of the syrinx by open myelotomy resulted in prompt relief and reversal of symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…10,13,17,23,27 Giant SB in childhood and fatal hemorrhage have been reported. 31,34,35 Intractable hiccups 4,33 have been observed in SB and SM, and in 1 case the hiccups resolved after posterior fossa surgery. 33 Another consistent observation we report relates to SB location: SB in the medulla was present in all of our 13 cases.…”
Section: Discussionmentioning
confidence: 99%
“…10,13,17,23,27 Giant SB in childhood and fatal hemorrhage have been reported. 31,34,35 Intractable hiccups 4,33 have been observed in SB and SM, and in 1 case the hiccups resolved after posterior fossa surgery. 33 Another consistent observation we report relates to SB location: SB in the medulla was present in all of our 13 cases.…”
Section: Discussionmentioning
confidence: 99%
“…8 Samples et al also reported on syringomesencephalia in the pre-MRI era. 25 There have been several publications since, 2,9,13,23,27 and a review of the literature was performed by Afifi and Menezes 1 in 1997 and subsequently by Greenlee et al in 2005. 7 Valentini and colleagues detailed an evaluation of 75 patients with syringomyelia, 8 of whom had a syringobulbic extension.…”
Section: Discussionmentioning
confidence: 99%